Surface electromyography analysis of mirror movements under unilateral movement in stroke patients: A retrospective study - Dai, Jie; Wu, Fangchao; Li, Jianhua; Yu, Mengjie; Liao, Chen; Shou, Yiqun (Frontiers in Human Neuroscience, 2022)
Objective: Mirror movements (MMs) are common abnormal motor performance in patients with poststroke hemiparesis. The study aimed to utilize the Electromyography (EMG) characterization of MMs in stroke patients and explore the relationship between MMs and the motor function of affected limbs. Methods: Sixty patients with stroke who had used to undergo clinical assessment and surface Electromyography (sEMG) were selected in this study. We investigated the relative excitation level (RE) and overflow percentage (OF) as a measure of mirror activities on bilateral muscles of stroke patients. Results: In stroke patients, mirror activities occurred in both affected and unaffected muscles during maximal contractions. We found that OF at unilateral contraction on the affected side (UCA) was significantly greater than that at unilateral contraction on the unaffected side (UCU). Additionally, a negative correlation between OF at UCA and Brunnstrom stages on admission and discharge. However, there were no significant correlations between OF and disease duration, Bathel Index, or the degree of improvement in all clinical evaluations. We still found a positive correlation between RE at UCA and the improvement of the Brunnstrom stage of the hand. But we could not find any significant correlation between RE and other clinical evaluation scores. Conclusion: In conclusion, the study found mirror activities in both affected and unaffected muscles, confirming an asymmetry between them. Although the mechanisms are still unclear, we confirmed a significant correlation between MMs at UCA and the motor function of the affected upper extremity, which might provide further evidences for understanding MMs in stroke patients and a new research direction on evaluation for motor function and outcomes of stroke patients.